Optimization of multipoint phase retrieval in edge illumination X‐ray imaging: A theoretical and experimental analysis. Issue 10 (29th August 2021) - Massimi, Lorenzo; Partridge, Tom; Astolfo, Alberto; Endrizzi, Marco; Hagen, Charlotte K.; Munro, Peter R.T.; Bate, David; Olivo, Alessandro
Abstract: Purpose : In this work, an analytical model describing the noise in the retrieved three contrast channels, transmission, refraction, and ultra small‐angle scattering, obtained with edge illumination X‐ray phase‐based imaging system is presented and compared to experimental data. Methods : In EI, images acquired at different displacements of the presample mask (i.e., different illumination levels referred to as points on the "illumination curve"), followed by pixel‐wise curve fitting, are exploited to quantitatively retrieve the three contrast channels. Therefore, the noise in the final image will depend on the error associated with the fitting process. We use a model based on the derivation of the standard error on fitted parameters, which relies on the calculation of the covariance matrix, to estimate the noise and the cross‐channel correlation as a function of the position of the sampling points. In particular, we investigated the most common cases of 3 and 5 sampling points. In addition, simulations have been used to better understand the role of the integration time for each sampling point. Finally, the model is validated by comparison with the experimental data acquired with an edge illumination setup based on a tungsten rotating anode X‐ray source and a photon counting detector. Results : We found a good match between the predictions of the model and the experimental data. In particular, for the investigated cases, an arrangement of the sampling points leading to minimum noise and cross‐channel correlation can be found. Simulations revealed that, given a fixed overall scanning time, its distribution into the smallest possible number of sampling points needed for phase retrieval leads to minimum noise thanks to higher statistics per point. Conclusions : This work presents an analytical model describing the noise in the various contrast channels retrieved in edge illumination as a function of the illumination curve sampling. In particular, an optimal sampling scheme leading to minimum noise has been determined for the case where 3 or 5 sampling points are used, which represent two of the most common acquisition schemes. In addition, the correlation between noise in the different channels and the role of the number of points and exposure time have been also investigated. In general, our results suggest a series of procedures that should be followed in order to optimize the experimental acquisitions.